Risk factors in relation to neurological morbidity in children: a study on perception of health professionals and parents - Adhikari, K. M.; Bhandari, Ashok (International Journal of Contemporary Pediatrics, 2019)
Background: Morbidity resulting from various neurological illnesses is a common reason for seeking regular help from health care facilities. There is increased requirement of awareness about neurological, psychiatric, physical, and developmental disorders in the community. Present study was undertaken to assess the community awareness and perception of risk factors for neurodevelopmental disabilities in children. Methods: The study was conducted with an objective of finding out level of awareness of a group of young health professionals and parents regarding their perception of likely factors that contribute for the occurrence of neurodevelopmental disabilities. This was a cross sectional study with discussion between the participants of various groups by using the method of Focused Group Discussions. Perceived risk factors as emerged during the discussions were free-listed and categorized under Biological/Familial/Genetic factors, Environmental factors, Socio-cultural factors and Economic/ Financial factors. Results: Lack of prenatal care, prematurity, unaffordability of care, low birth weight, malnutrition, infections and lack of maternal education emerged as important risk factors for neuromorbidity as perceived by the participants. Participants also enumerated insufficient knowledge on preventable risk factors, lack of trained manpower and neglect of female children as important contributors to occurrence of developmental disabilities. Conclusions: It is of paramount importance to identify the community perception of the risk factors for developmental disability which gives us an estimate of awareness among people and caregivers. Interventions tailored to the needs based on the level of community awareness help us in better channelling of preventive programmes and strategies.